Drug addict’s experiences on oral health care: an interview study - Lange, Martin Bergseng; Thorsteinsson, E. B. (Universitetet i Tromsø, 2011)
Objective: To understand the dental health challenges of recovered drug addicts, and how the system of oral health rehabilitation works and functions as seen from the perspective of recovered addicts. Basic Design: Semi-structured interviews with seven recovered drug addicts from the city of Tromsø, Norway. The audio from the interviews was transcribed and analysed using NVIVO software. Results: All informants had experienced or were experiencing oral health problems related to their history of drug abuse. These problems adversely affect their quality of life. The care-seeking process was perceived as challenging by some informants; both in the case of obtaining emergency treatment when they were active addicts, and in relation to full oral health rehabilitation when enrolled in drug rehabilitation programs. Also, some groups of addicts were found to be left out of the legislative framework of the system. Conclusion: The system of oral health rehabilitation for recovered drug addicts has undergone legislative changes over the later years. This seems to have made the system somewhat more effective and including, but there are still groups left outside the system that, it could be argued, should be included. Also, challenges exist in conveying to drug addicts the possibilities for financial aid for emergency treatment.